Rancang Bangun Robot ASR (Automated Storage And Retrieval) 3 Axis Untuk Peminjaman Instrumen Di Laboratorium Electric Drive - Alhilal, Mustaqim; Hajah, M. Sohibul; Kurdianto, Akhmad Arif (Politeknik Negeri Madura, 2022)
The development of science and technology today is growing very fast. This makes students compete to keep up with technological developments in the era of digitalization. Madura State Polytechnic through electric drive laboratory facilities requires practicum supporting equipment. In borrowing instruments for practical needs, data collection and others can be done very easily and quickly. The process of storing or retrieving instruments in the laboratory, taking instruments on a shelf still uses conventional methods. An automated system can be applied to the storage and retrieval process of laboratory instruments to make the process faster, easier, and have high accuracy. This study tries to help solve problems in the instrument storage and retrieval system which is still at the conventional stage to be developed into an online based. From the experiments that have been carried out, the ASR Robot is controlled using a Programmable Logic Controller (PLC) which functions as the main control of the automatic instrument storage and retrieval system. Proximity sensors are used to detect the position of the robot and limit the movement of the robot so that it is accurate to pick up instruments that are in stacked shelves. The ASR robot works by requiring 294.8 Watts of power.